2019
DOI: 10.3390/molecules24163009
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chitosan in Bone and Dental Engineering

Abstract: Chitosan is a deacetylated polysaccharide from chitin, the natural biopolymer primarily found in shells of marine crustaceans and fungi cell walls. Upon deacetylation, the protonation of free amino groups of the d-glucosamine residues of chitosan turns it into a polycation, which can easily interact with DNA, proteins, lipids, or negatively charged synthetic polymers. This positive-charged characteristic of chitosan not only increases its solubility, biodegradability, and biocompatibility, but also directly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 146 publications
(97 reference statements)
1
144
0
1
Order By: Relevance
“…Among these there are bioactive glasses (BGs), which are commonly used as promising scaffold materials for bone and soft tissue regeneration [19]. For orthopedic applications, different composite nanofiber scaffolds have been developed using CS and other polymers and incorporating bioactive glasses [20][21][22][23][24]. However, in literature no comparison of these composite coatings with uncoated titanium alloys has been yet provided in order to evaluate effectively the antibacterial effect and the simultaneous osteoconductive activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among these there are bioactive glasses (BGs), which are commonly used as promising scaffold materials for bone and soft tissue regeneration [19]. For orthopedic applications, different composite nanofiber scaffolds have been developed using CS and other polymers and incorporating bioactive glasses [20][21][22][23][24]. However, in literature no comparison of these composite coatings with uncoated titanium alloys has been yet provided in order to evaluate effectively the antibacterial effect and the simultaneous osteoconductive activity.…”
Section: Introductionmentioning
confidence: 99%
“…The great variety of applications of chitosan in the field of biomaterials is due to its excellent properties when interacting with the human body: bioactivity [11], antimicrobial and antifungal activity [12,13], immunostimulation [14], chemotactic action, enzymatic biodegradability, mucoadhesion, and epithelial permeability [15], which supports the adhesion and proliferation of different cell types [16]. With the above properties, CHI derivatives serve a broad range of applications and these materials have advanced at a dramatic pace into many fields, including skin, wound, and burn management [17]; drug delivery and pharmaceutical applications [18]; tissue engineering [19]; dentistry [20]; plant science and agriculture [21]; veterinary science [22]; cosmetics and cosmeceutical [23]; food and nutraceuticals [24]; and, paper industry [25], among others.…”
Section: Introductionmentioning
confidence: 99%
“…This biomaterial is biocompatible, biodegradable, and osteoconductive, facilitating the adhesion and proliferation of cells on its surface. The CS-based scaffold can be combined with other polymers and molecules in order to improve its mechanical and biological properties [48,49]. As a confirmation of this, in all the selected studies the data obtained from the analysis of the mineralization level, cell proliferation/viability, and alkaline phosphatase activity demonstrated that pure chitosan scaffolds were less effective at regenerating the bone tissue than the chitosan-based scaffolds combined with other biomaterials, molecules, and stem cells.…”
Section: Discussionmentioning
confidence: 68%